Sistem Informasi Pengupahan Pada Ternama Konveksi Berbasis WEB - Sophia Nurhafshoh Koesnady; Avid Inang Rum (IPSIKOM, 2025)
This study aims to analyze, design, implement and test the wage information system at Ternama Konveksi based on WEB. In this study the author obtained data by conducting observations, interviews and literature studies. The development carried out to overcome these problems is using the waterfall method and PIECES analysis by finding weaknesses in the running system. This wage information system is designed using a programming language with HTML (Hypertext Markup Language) database software, PhpMyAdmin, MySQL, XAMPP, Visual Studio Code, then tested with black box testing. In data processing, users only input data into the system then data processing will be carried out by the system until the creation of wage reports and employee pay slips. The results of the wage information system test have fulfilled its function according to the proposed design and can be a solution related to the wage information system at Ternama Konveksi in the process of calculating and paying employee wages.